Spirulina platensis GROWTH IN POLLUTED DOMESTIC WASTE WATER MEDIUM AND ITS UTILIZATION AS A RAW MATERIAL FOR BIOGAS PRODUCTION - Sinaga, Rugun; Effendi, Irwan; Mubarak, Mubarak; Ambarsari, Hanies (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted in April - June 2019, located at the Center for Environmental Technology Laboratory (PTL) - Agency for the Assessment and Application of Technology (BPPT), Building 820 Geostech, Puspitek Serpong, South Tangerang. The purpose of this study was to determine the biogas production from S. platensis microalgae grown in polluted domestic waste media from Muara Angke waters with different concentrations. The method used in this study is an experimental method with a Completely Randomized Design (CRD) with 3 different treatments of S. platensis concentrations consisting of 5% v/v, 15% v/v and 25% v/v performed three repetitions with the addition cow manure substrate and control without the addition of cow manure substrate. The parameters observed were physical parameters, chemical parameters, biomass calculations and biogas volume measurements. Data were analyzed and tested statistically using Analysis Of Variance (ANOVA) and further tested using the LSD test to compare between treatments with a 95% confidence level. Biogas is energy that can be used as an alternative fuel to replace fossil fuels such as petroleum and natural gas. The results showed that S. platensis with the addition of cow dung could produce more biogas volume (4453.6 cm) than S. platensis without the addition of cow dung (697.19 cm). Biogas volume is measured using the gas holder method.